Flexural Strength of Interlocking Compressed Earth Brick (ICEB) Unit - Saari, S.; Bakar, B. H. Abu; Surip, N. A. (IPTEK Journal of Proceedings Series, 2017)
This paper presents the flexural strength of the ICEB unit. The flexural strength is important in determining the strength of the masonry unit. About 260 units of ICEB consist three type of unit were tested on flatwise (bed direction) and inverted direction, with the different shape at the top and bottom of the ICEB. The unit was loaded at midspan through a steel bearing plate of 6.4 mm thickness and 38.1 mm width. Specimens were supported at both ends which are free to rotate in the longitudinal and transverse directions during the test. The highest flexural strength of ICEB is Wall Brick for both flatwise and inverted direction which is 2.36 N/mm2 and 2.15 N/mm2, respectively. For flatwise direction, Beam Brick has the lowest flexural strength which is 1.55 N/mm2, and in inverted direction Column Brick flexural strength is lower than Beam Brick which is 1.65 N/mm2. ICEB can be used in construction and has the equal properties as other common brick and block at the market nowadays.